Impacts by feral goats on critically endangered Crepidiastrum grandicollum (Compositae) endemic to the Ogasawara Islands. Issue 2 (2nd February 2021) - Abe, Tetsuto
Abstract: Oceanic islands are biodiversity hotspots with highly endemic ecosystems that are vulnerable to invasive alien species. Understanding the status of endangered species and identifying threats have the highest priority for insular biodiversity conservation. The two remaining populations of endangered Crepidiastrum grandicollum on Chichi‐jima Island were studied for 5 years to describe their status and evaluate the impacts of feral goats ( Capra hircus ). The main cause of population decline was browsing by goats. The populations protected by the exclosures were stable but declined after an exclosure was removed. Even in the protected population, regeneration was limited outside the exclosures and in 1 year of the survey, a high proportion of feeding damage by moth larvae was observed in one population. These facts indicate that exclosures are not a sufficient conservation measure, and eradication of goats and population restoration in novel habitats are necessary to reduce the extinction risk of C. grandicollum . Abstract : I report the critical status of endangered Crepidiastrum grandicollum endemic to the Ogasawara Islands. Without the exclosure fence, the population was declining due to the feeding damage by feral goats, and even if the population was surrounded by exclosure, feeding by moth larvae posed another threat. These facts suggest that the installation of exclosures alone is not enough to reduce the extinction risk of C. grandicollum .